Modulation of host gene expression by the zinc finger antiviral protein - Daniel Gonçalves-Carneiro; Emily Mastrocola; Xiao Lei; Paul D. Bieniasz (Proceedings of the National Academy of Sciences, 2025)
The zinc finger antiviral protein (ZAP) depletes nonself RNAs through recognition of their elevated CpG dinucleotide content. CpG dinucleotides are sparse in most endogenous mammalian mRNAs, but a subset might potentially be modulated by ZAP. While CpG frequency alone is insufficient to predict ZAP-regulation, we developed an algorithm using experimentally determined compositional features to predict which endogenous mRNAs may be ZAP-regulated. Using ZAP-knockout mice, we demonstrate that levels of many host mRNAs that are algorithmically predicted ZAP targets are indeed increased when ZAP is absent. ZAP is interferon-inducible, and we also identify genes that are downregulated by ZAP during an innate immune response. Many ZAP-regulated gene products are extracellular matrix or of nucleosome components, whose ZAP-mediated control is conserved in human cells. Overall, we provide a tool for the prediction of ZAP target genes and reveal host mRNAs that are ZAP-regulated.